Legality Of E-Commerce Transactions: A Comparative Analysis Of Islamic Law And Indonesian Civil Law - Irlina Dewi; Yuni Dhea Utari; Asfar Hamidi Siregar; Rino Riyaldi (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
The development of information technology has encouraged the emergence of increasingly complex e-commerce transactions that require legal certainty. This study aims to analyze the legality of e-commerce transactions through a comparison of Islamic law and Indonesian civil law perspectives. The method used is normative juridical research with a descriptive-analytical approach based on literature review, using primary sources in the form of the Qur'an, hadith, the Civil Code, the ITE Law, and fatwas of contemporary scholars, and secondary sources in the form of related academic literature. The results of the study indicate that in Islamic law, e-commerce transactions are permitted as long as they fulfill the pillars and conditions of a valid sale and purchase, are free from elements of gharar, usury, and fraud, and uphold the principles of justice, honesty, and openness. Meanwhile, Indonesian civil law views e-commerce as valid if the conditions of an agreement as stipulated in Article 1320 of the Civil Code are met, namely the existence of an agreement, legal capacity, a specific object, and a lawful cause, and are based on the principles of freedom of contract and good faith. Thus, both Islamic law and civil law emphasize the importance of transparency, agreement, and justice, although with different emphases. This study recommends strengthening regulations and legal education to protect consumers while creating a safe and equitable digital transaction ecosystem.